Changes in WHO Z-scores by Gender in Stunting Children of Cipamokolan Public Health Center (2023–2025) - Fajar Awalia Yulianto; Diany Maedasari; Diana Endah Nurul Rachman (UPT Publikasi Ilmiah Universitas Islam Bandung, 2026)
Indonesia’s stunting prevalence exceeds the World Health Organization's threshold of 20%. While nutritional interventions account for 30% of the reduction in stunting, there is no conclusive evidence linking gender directly to stunting outcomes. In 2023, Bandung Regency reported the highest stunting prevalence in West Java Province. This study aimed to analyze the differences in stunting outcomes between boys and girls at a public health center (Cipamokolan) in Bandung Regency. We employed a retrospective cohort design to assess changes in Z-scores (height/length-for-age status) among male and female children aged 0 to 59 months over a 2-year follow-up period, using Cox regression. The study included 153 stunted children, with a majority being males (65.4%). During follow-up, only 7.8% of the children showed an increase in their Z-scores (catch-up), while most (79.1%) maintained their stature. Unfortunately, 13.1% of the children experienced a decline in their Z-scores compared to previous examinations. The hazard ratio (HR) for sex and decreased Z-scores was 1.19 (95% CI=0.46–3.11), indicating no significant difference in worsening stunting cases between boys and girls. Stunting intervention strategies should be implemented equally for all children, regardless of gender, with special attention to treatment management. The lack of improvement or decrease in Z-scores over 2 years indicates a poor outcome from the interventions and requires urgent attention.